On Parallel Fast Jacobi Algorithm for the Eigenproblem of Real Symmetric Matrices (Journal of Computational Mathematics, 2021)
Jacobi algorithm has been developed for the eigenproblem of real symmetric matrices, singular value decomposition of matrices and least squares of the overdetermined system on a parallel computer. In this paper, the parallel schemes and fast algorithm are discussed, and the error analysis and a new bound are presented.